Comparative study of oxazolidine and imidazolidine compounds as inhibitors of SAE 1020 steel corrosion in aqueous HCl solution - Silva, Matheus Gomes; Costa, Alberto Nei Carvalho [UNESP]; Sangi, Diego Pereira; Yoneda, Julliane; Coelho, Lilian Weitzel; Ferreira, Elivelton Alves (Taylor & Francis, 2021)
In many industries, safe organic inhibitors that are soluble in corrosive media, environmentally friendly, and effective need to be developed for protection against corrosion during descaling and steel pickling in dilute acids. In this work we describe, for the first time, the effects of 2-(nitromethylene) oxazolidine (OXA) and 2-(nitromethylene) imidazolidine (IMD) as inhibitors of the corrosion of SAE 1020 steel in 0.1 mol L−1 HCl aqueous solution. Electrochemical analyses showed that the IMD inhibitor was most effective, acting as a mixed type inhibitor. SEM analysis confirmed the electrochemical results, clearly showing the excellent corrosion inhibition effect of IMD. The corrosion inhibition was related to the protective film deposited on the surface, forming a layer that reduced the corrosion reactions. DFT calculations showed that donor and acceptor interactions between the heterocyclic nitrogen lone pair electrons and the vacant d orbitals of the metal surface atoms could explain the better corrosion inhibition values obtained for IMD. Finally, in addition to its efficiency, in silico toxicity predictions indicated that IMD could be considered environmentally friendly.
Keywords: Corrosion inhibition; density functional theory; electrochemical impedance spectroscopy; imidazolidine; oxazolidine; polarization curves